Filipina representations a content analysis on Women's Journal Magazine, 1986-2006 - Amparo, Ariane Erin C.; Mariano, Claudine D.; Serona, Donna A. (2007)
"Filipina Representation" is a content analysis of Women's Journal Magazine and how women have been represented over three decades - from 1986 to 2006. It identified five sections of the magazine showing women representations, namely: cover story, "Make- Over Magic," features, fashion photos, and advertisements. Then, it aimed to find out how Women's Journal has adapted to the major social changes in the country as reflected in these sections. And third, determined the significant changes in the representation of women. The significance of the study targeted towards the readers of the magazine, that they be more critical in both reading and perceiving women in general. This study used three theories as frameworks - Agenda Setting Theory, Uses and Gratifications Theory, and the concepts of the Feminist Theory. Based on the results and discussions, the researchers came out with three main conclusions. First, women are represented as physically beautiful. The magazine follows the standards of beauty or the expectations of what a woman should look like, and how she should act based on norms set by society. Usually, they are trapped in certain images like wife and mother, at the same time, still appealing to the opposite sex. Also, the magazine adapted to social changes with women represented as an empowered gender. Lastly, the researchers concluded that women representation changed through time, from modern to liberated. Given the limited scope of the study, the researchers recommend further studies about the reader's perception towards the content of Women's Journal. Moreover, the magazine's contemporary marketing strategy and organizational structure could be studied. Other sections (e.g teen-oriented sections) may be covered in another content analysis -- Author's abstract.